Digital Predictions: Children’s Futures, Opportunities and Obstacles - Willson, Michele (Springer, 2021)
Early childhood is seen by many as the ideal time to shape, support and encourage the child in order to become fully emotionally, intellectually and socially competent adults in the future. Discussions about the degree that children can participate and have agency in these processes are ongoing. However, what happens with these agentic capacities when decisions are made based on big data analytics and predictive algorithms?